2018
DOI: 10.1093/mnras/sty458
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational lensing reveals extreme dust-obscured star formation in quasar host galaxies

Abstract: We have observed 104 gravitationally-lensed quasars at z ∼ 1-4 with Herschel/SPIRE, the largest such sample ever studied. By targeting gravitational lenses, we probe intrinsic farinfrared (FIR) luminosities and star formation rates (SFRs) more typical of the population than the extremely luminous sources that are otherwise accessible. We detect 72 objects with Herschel/SPIRE and find 66 percent (69 sources) of the sample have spectral energy distributions (SEDs) characteristic of dust emission. For 53 objects … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
104
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(120 citation statements)
references
References 177 publications
16
104
0
Order By: Relevance
“…1). This combination is consistent with the overall FIR-radio spectral energy distribution of MG J0414+0534 (Stacey et al 2018). The total flux-density is S 340 GHz = 24.3 ± 1.2 mJy, of which about 50 percent is contained in the compact images.…”
Section: Continuumsupporting
confidence: 83%
See 1 more Smart Citation
“…1). This combination is consistent with the overall FIR-radio spectral energy distribution of MG J0414+0534 (Stacey et al 2018). The total flux-density is S 340 GHz = 24.3 ± 1.2 mJy, of which about 50 percent is contained in the compact images.…”
Section: Continuumsupporting
confidence: 83%
“…Second, interferometric arrays such as ALMA can provide sufficiently high angular resolution (> 10 mas) such that any degeneracies between the inferred level of substructure and the source model (often assumed to be point-like) can be minimised. Finally, 70 percent of known gravitationally lensed quasars are FIR-bright (Stacey et al 2018), and so are expected to have detectable high excitation gas associated with the quasar. This, coupled with the large-scale lens surveys being carried out with DES, for example, will provide a large population of potential targets for this work in the near-term.…”
Section: Discussionmentioning
confidence: 99%
“…RQQ PG 1115+080 has also been observed by Stacey et al (2018). Again, a relatively high dust temperature has been measured, suggesting that the object lies, with HS 0810+2554, on the radio-FIR correlation of Ivison et al (2010), yet X-ray observations by Chartas et al (2003) have again found evidence for a relativistic gas outflow.…”
Section: Discussionmentioning
confidence: 87%
“…Of further significance is that the FIR luminosity measurements made by Stacey et al (2018) found that HS 0810+2554 does not display the expected radio excess from the radio-FIR correlation typically associated with AGN activity. While we have found clear evidence for jetdominated radio emission, observations of X-ray absorbing gas by Chartas et al (2014Chartas et al ( , 2016 within HS 0810+2554 found evidence for a relativistic gas outflow.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, gravitational lenses magnify the high redshift Universe, allowing detailed studies of galaxies that otherwise would not be detectable with current instruments (e.g. Barvainis & Ivison 2 C. Spingola et al 2002;Impellizzeri et al 2008;Riechers et al 2011;Sharon et al 2016;Stacey et al 2018).…”
Section: Introductionmentioning
confidence: 99%